(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
The productive impact of gastrointestinal nematodes (NGI) of small ruminants are known worldwide. Infestations by NGI constitute a limiting factor in the production of ruminant and the losses included by this sanitary problem vary from subclinical reductions in weight gain to the death of animals with high parasite loads. The objective of this work is to present the results of an efficacy trial using a commercial combination of Abamectin + Derquantel and Moxidectin in dairy goats naturally infested with NGI in the Lerma Valley, Salta province. The test was carried out in the Dairy Goat Unit of the Salta Agricultural Experiment Station of INTA. In the pretreatment stool cultures, a high prevalence of Trichostrongylus spp. (71%). followed by Teladorsagia spp. (21%) and Haemonchus spp. (8%) was observed. Regarding the results of the TRCH, in the GDQ values ​​of 100% of PRCH were observed, while in the GMX a PRCH of 95.5% is shown, where the efficacy for Haemonchus spp. and Teladorsagia spp. was 100% and for Trichostrongylus spp. 81.1%. The results observed in this work allow us to conclude that under the field conditions where TRCH was carried out, the Derquantel-Abamectin combination has high efficacy against the genera present.